HUBUNGAN ANTARA KECANDUAN INTERNETDENGAN PROKRASTINASI TUGAS SEKOLAH PADA REMAJA PENGGUNA WARNET DI KECAMATAN MEDAN KOTA - Miranda Julyanti; Siti Aisyah (Faculty of Psychology, Universitas Medan Area, 2015)
This studyaimed to determinethe relationshipbetween internet addictionwithprocrastination of school work. Subjectswere youth of internet caféusersin the district ofMedanKota, samples were takenwith purposive sampling technique. Data collection toolused is the internet addictionscaleandthe procrastination of school work scale. Analysis of datausing the Product Moment correlation technique from Pearson. Based onanalysis ofdata, found that thehypothesis presentedin this studyreceived, that there isa positive relationship between internet addiction to procrastination of school work at youth of internet caféusersin the district ofMedanKota. This is evidenced bythe correlationcoefficientrxy = 0,770 withρ=0.000, while thecoefficientof determination(r²) of 59.3%. The result ofthe empirical meanandhypothetical mean obtained that internet addiction classified aslikely to be high (107.60>105)and procrastination of school work quitetends to be high (98.87>95).Key words: Internet addiction,procrastinationofschool work